Prevalence and Associated Factors of Frailty in Patients with Chronic Heart Failure: A Systematic Review and Meta-Analysis - Longren Wu; Si Liu; Meijun Zhang; Xiaoyun Xiong (Reviews in Cardiovascular Medicine)
Background: Although numerous studies have investigated the prevalence of chronic heart failure (CHF) and the factors influencing frailty in patients with CHF, the findings remain inconsistent. Therefore, this review aimed to systematically evaluate the prevalence and associated frailty factors in patients with CHF to establish an evidence-based foundation for risk assessment and treatment strategies. Methods: A comprehensive search was conducted across multiple databases, including EMBASE, the Cochrane Library, PubMed, Web of Science, CINAHL, Chinese Biological Medicine (CBM), CNKI, and Wan Fang up to August 25, 2024. The objective was to identify observational studies that examined factors influencing frailty in CHF patients. The quality of the selected studies was evaluated using appropriate assessment tools, and a meta-analysis was performed to determine the relevant factors associated with frailty in this population. Results: A total of 23 articles containing 6287 patients were included. The prevalence of frailty in patients with CHF was 39% (95% confidence interval (CI): 0.33–0.45). Factors shown to be positively associated with frailty in CHF patients were older age, cerebrovascular accidents, longer hospital stay, larger left atrial diameter, higher number of comorbidities, poor New York Heart Association (NYHA) functional class, and poor sleep quality. Conversely, higher albumin, hemoglobin, and left ventricular ejection fraction (LVEF) levels were negatively associated with frailty. Conclusions: The prevalence of frailty in patients with CHF is relatively high and varies according to different assessment tools applied. Thus, establishing specific frailty assessment tools for CHF patients and providing targeted interventions based on important factors are essential for reducing the burden of frailty and improving outcomes. The PROSPERO registration: CRD42023448771, https://www.crd.york.ac.uk/PROSPERO/view/CRD42023448771.